A research agenda for public diplomacy - Gilboa, Eytan; Edward Elgar Publishing (Northampton : Edward Elgar Publishing, 2023)
"Elgar Research Agendas outline the future of research in a given area. Leading scholars are given the space to explore their subject in provocative ways, and map out the potential directions of travel. They are relevant but also visionary. Public diplomacy has become one of the central instruments of foreign policy and national security; this crucial Research Agenda provides a new outline for its investigation. Aiding the comprehension of the broad boundaries of the field, it proposes a clear starting point for contemporary research into important areas of public diplomacy. This enlightening Research Agenda is divided into three parts which thoroughly explore the actors, disciplines and instruments involved in the process of public diplomacy. Rich in innovative analysis, chapters offer insights from many of the most prominent scholars and practitioners in the field to cover existing research, gaps, and future directions. A Research Agenda for Public Diplomacy will be invaluable for researchers and students interested in political science, international and public relations, communication, and digital media. It will also be beneficial for practitioners and officials working in areas relevant to foreign policy and national security employed by both governmental and non-governmental organizations"--
Contents: Preface -- Acknowledgments -- 1. Moving to a new phase in public diplomacy research / Eytan Gilboa -- Part I. Actors -- 2. States: Public diplomacy contests in asia / Caitlin Byrne -- 3. International organizations / Phillip Arceneaux -- 4. Corporate diplomacy / Candace L. White and Wilfried Bolewski -- 5. City diplomacy / Efe Sevin and Soheala Amiri -- 6. Citizen diplomacy / Paul Lachelier and Sherry L. Mueller -- Part II. History -- 7. History / Nicholas J. Cull -- 8. International relations / Craig Hayden -- 9. Public relations / Kathy R. Fitzpatrick -- 10. Relational and collaborative approaches / R.S. Zaharna and Amelia Arsenault -- 11. Disinformation / Alicia Fjällhed and James Pamment -- 12. Management / Steven L. Pike -- Part III. Instruments -- 13. Cultural diplomacy / Natalia Grincheva -- 14. Nation as brand / Simon Anholt -- 15. International broadcasting / Shawn Powers -- 16. International exchanges / Giles Scott-Smith -- 17. Digital public diplomacy / Ilan Manor -- 18. Hybrid communication / Jian Wang and Jack Lipei Tang -- Index.
Includes bibliographical references and index.
Description based on print record.
Keywords: elektronické knihy; electronic books; Public relations; Diplomacy